HUBUNGAN ANTARA MANUSIA DAN LINGKUNGAN DALAM NOVEL RAHASIA PELANGI KARYA RIAWANI ELYTA DAN SHABRINA WS: EKOLOGI SOSIAL - Akhmad Idris (Kantor Bahasa Provinsi Maluku Utara, 2022)
In the midst of the climate crisis issue as it is today, literary works have started to appear on the topic of ecology. One of them is the novel Rahasia Pelangi by Riawani Elyta and Shabrina WS which is set in natural conditions in the Riau region. The novel Secret of the Rainbow raises environmental issues regarding the conflict between elephants and the Tesso Nillo community. The characters in the novel Secret of the Rainbow are described as environmental fighters who work for the Environmental NGO, CWO (Change World Organization). They focus on handling cases of human-elephant conflict in Riau. Not only presenting natural problems in the form of physical damage to nature, but also the relationship between humans and nature in a social context. Therefore, this research focuses on social ecology. This research is a qualitative descriptive study that aims to thoroughly describe social ecology in the novel Rahasia Pelangi by Riawani Elyta and Shabrina Ws. The results of the analysis of social ecology in the novel Secret of the Rainbow by Riawani Elyta and Shabrina WS show that the characters in the novel reflect the interaction between humans and nature. Humans influence natural conditions through their outlook on life. Nature influences the human condition in terms of lifestyle, welfare, religious and cultural activities.